Grammar Learning Strategy Inventory (GLSI): Another look - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2018)
Despite all the progress that has been made in research on language learning strategies since the publication of Rubin’s (1975) seminal paper on good language learners, there are areas that have been neglected by strategy experts. Perhaps the most blatant manifestation of this neglect is the paucity of research into grammar learning strategies (GLS). The main premise of this paper is that for such research to gain momentum, it is to necessary to create valid and reliable data collection instruments that would enable tapping the use of different types of GLS. In line with this reasoning, the article reports a study that aimed to determine the psychometric properties of the Grammar Learning Strategy Inventory (GLSI), a tool constructed by Pawlak (2009b, 2013) on the basis of his classification of strategies for learning grammar in a second or foreign language. Exploratory factor analysis was also employed with the purpose of uncovering the underlying structure of strategic learning of grammar. The analysis provided evidence for largely satisfactory validity and reliability of the GLSI, indicating at the same time there is room for improvement, with concrete changes being possible after the instrument has been tested with a much larger sample.